2003
DOI: 10.4049/jimmunol.170.8.4254
|View full text |Cite
|
Sign up to set email alerts
|

TCR Vβ8+ T Cells Prevent Development of Toxoplasmic Encephalitis in BALB/c Mice Genetically Resistant to the Disease

Abstract: BALB/c are genetically resistant to development of toxoplasmic encephalitis (TE) when infected with Toxoplasma gondii, whereas CBA/Ca mice are susceptible. We compared TCR Vβ chain usage in lymphocytes infiltrated into brains between these animals following infection. TCR Vβ8+ cells were the most frequent T cell population in brains of infected, resistant BALB/c mice, whereas TCR Vβ6+ T cells were more prevalent than Vβ8+ T cells in brains of infected, susceptible CBA/Ca mice. Adoptive transfer of Vβ8+ immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Indeed, it was demonstrated that a higher frequency of Vβ8 chain in T lymphocytes was associated with BALB/c (H2 d ) resistance against TE caused by ME49, whereas preferential Vβ6 chain usage corelated with susceptibility in CBA/Ca (H2 k ). Adoptive transfer of BALB/c Vβ8 + , but not Vβ6 + , T cells was capable to prevent mortality and encephalitis in nude mice (Kang et al 2003, Wang et al 2005. Another evidence of the importance of cell-mediated effector mechanisms is that neutralization of IFN-γ or TNF-α and inhibition of NOS2 leads to reactivation of chronic infection with ME49 and results in encephalitis and uveitis (Gazzinelli et al 1992, 1993a, 1994a, Hayashi et al 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was demonstrated that a higher frequency of Vβ8 chain in T lymphocytes was associated with BALB/c (H2 d ) resistance against TE caused by ME49, whereas preferential Vβ6 chain usage corelated with susceptibility in CBA/Ca (H2 k ). Adoptive transfer of BALB/c Vβ8 + , but not Vβ6 + , T cells was capable to prevent mortality and encephalitis in nude mice (Kang et al 2003, Wang et al 2005. Another evidence of the importance of cell-mediated effector mechanisms is that neutralization of IFN-γ or TNF-α and inhibition of NOS2 leads to reactivation of chronic infection with ME49 and results in encephalitis and uveitis (Gazzinelli et al 1992, 1993a, 1994a, Hayashi et al 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…To determine TCR Vβ chain usage in the CD8 + immune T cells that had infiltrated into the brains of the recipient SCID mice, the purified mononuclear cells were first pretreated with anti-FcγII/III receptors mAb (clone 2.4G2) and then incubated with a PE-conjugated mAb to CD8α (clone 53–6.7) and FITC-conjugated mAb to various TCR Vβ chains as described previously (18). The mAbs were from BD Bioscience, and the staining was performed using pooled cells from the mice due to availability of only limited numbers of cells from the brain of each animal.…”
Section: Methodsmentioning
confidence: 99%
“…The brain is uniquely isolated from its own vasculature by the blood-brain barrier (BBB) (26), and yet CD8 + T cells in the bloodstream can cross into brain parenchymal tissue during infection (27,28), cancer (29)(30)(31), and autoimmune disease (32,33). Recent studies report that local antigenic stimulation may be required either for CD8 + T cell retention and motility arrest in brain microvasculature or crossing the BBB (34)(35)(36).…”
mentioning
confidence: 99%